A Significant Reducing Misconception on Newton’s Law Under Purposive Scaffolding and Problem-Based Misconception Supported Modeling Instruction - Suwasono Purbo; Koes H Supriyono; Adi P Nugroho; Saniso Eleeyah (Open Education Studies)
Despite continued efforts to address this issue, many students still exhibit misunderstandings regarding Newton’s laws. These misconceptions include beliefs, such as every movement requires a force, that force is directly proportional to velocity, and that action–reaction forces can differ in magnitude. To mitigate these misunderstandings, innovative teaching strategies like cognitive conflict approaches are essential. This study utilized a scenario-based scaffolding method, integrating common student misconceptions early in the modeling instruction (MI) process. This process requires scaffolding and authentic problems. To date, scaffolding in MI learning was not initially designed with students’ diversity in mind. The problems given by teachers in the early MI emphasize natural phenomena or symptoms that are aligned with the learning objectives in the curriculum. In contrast to what has been done, the force concept inventory (FCI) and interviews were used to pinpoint these misconceptions. The FCI was also administered as both a pretest and posttest to evaluate students’ reasoning abilities. Additionally, interviews provided deeper insights into the effectiveness of the instructional model in addressing persistent misconceptions. The combined data from interviews and test results revealed a significant improvement in students’ understanding of Newton’s laws, with a 65.42% reduction in misconceptions. The designed MI with scaffolding and the problems based on students’ misconceptions, fostering new and correct thinking patterns of students in responding to the natural phenomena in their daily lives.